IMPLEMENTASI KURIKULUM SEKOLAH DASAR BERBASIS PENDIDIKAN MULTIKULTURAL UNTUK MENGATASI DAMPAK NEGATIF INTERNET DAN GADGET PADA PESERTA DIDIK - Intan Kumala Dewi; Fitri Puji Rahmawati; Anik Ghufron (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The development of technology in the era of globalization may have a negative impact on students. Technology provides easy access to information, values and norms that are not in accordance with the values and norms of the Indonesian nation. Young learners are not fully capable of filtering the information, which can lead to moral degradation. This research aims to examine how multicultural education-based curriculum approaches and models to overcome the negative impact of gadgets and the internet on students in the classroom learning process in instilling multicultural values. This research design is a literature study. The results showed that in implementing multicultural education, the role of educators is needed in instilling life values in shaping individual characters that reflect the nation's identity. Multicultural education as a field of study also needs to continue to be the main concern in education in Indonesia so that if a certain condition occurs or even the next global revolution, the implementation of this multicultural education approach remains relevant to multiculturalism and nationalism in Indonesia.